Use of 365 nm fluorescence dermoscopy for diagnosis of pityriasis versicolor in a toddler. - Patil, S.; Dundi, V.K.; Bahuguna, A. (European Journal of Pediatric Dermatology, 2025)
Pityriasis versicolor, a superficial fungal infection caused by Malassezia species, is not uncommon in children. A 15-month-old boy with hypopigmented macules on the face, trunk, and upper and lower extremities was reported. Diagnosis was facilitated by 365-nm fluorescence dermoscopy, which revealed a characteristic yellow-green fluorescence, allowing rapid confirmation of the diagnosis. This case highlights the utility of fluorescence dermoscopy as a noninvasive diagnostic tool.